Project Feasiblity Study Alco-Diesel - Arsenal, Ray; Gonzales, Cesar, Jr; Herrera, Eric; Inocencio, Romeo, Jr (College of Engineering, 1997)
The Alco-diesel fuel blend is proudly a Filipino invention which recently received a patent. It is a superior fuel formula that increases the efficiency and mileage of diesel engines without engine modifications. If used extensively, this fuel has the potential to extend the use of the country's diesel supply be 15% and thus, correspondingly reduced diesel fuel importation. Moreover, the Alco-diesel fuel significantly reduces smoke emissions and the pollution from diesel engines. It helps protect the environmental balance. It also helps prevent motorists from being apprehended for smoke belching. The proposed project aims to expand the commercial production od duel to jump beyond the break-even point of operations. The project is envisioned to produce at least 80,000 liters of Alco-diesel fuel everyday to service the large Bus Companies in Metro Manila. Based on the market study, alco-diesel has the potential to survive and grow with its competitors. It shall cater to the land transport industry operating in the NCR with target market shares from the 16% of the NCR forecast of diesel consumption up to 20% by 2002. To attain this share, the company has to budget P523,000 for advertisement and promotions. The plant shall be located in the DOST-complex in Taguig MM to cater to both its raw materials suppliers and alco-diesel consumers. The diesel and methanol (RM's) shall be subcontracted or bought from the chosen suppliers. With the use of Mr. Rudy Lantano's invention, the agitating machines, production of alco-diesel can reach up to 81,000 L per day, one shift and 80% machine efficiency. Total project costs amounts to 269,921,380 broken down into 78,082,000 pesos for fixed investments, 623,000 pesos for start-up costs, 24,538,307 pesos for contingency allowance and 166,822,396 pesos for its working capital. Sources of financing will be from selling of common stocks and loan financing through the DBP. Expected sales ranges from 171 to 288 million pesos a year. Income from operations before repayment of loans to be ranging from P45,000,000 to P66,500,000 annually. Internal rate of return is 17.23% greater than MARR of 12% offered by financial institutions which measures the relative profitability of the product. Payback is 4 years and 3 1/2 months. The company shall have a workforce of 37, including managers to operate the company. IT shall be registered as a corporation under the name RL enterprises. Based on tests conducted by the DOST, the product is a superior fuel blend. The public can benefit by the reduction of smoke belching vehicles through the use of alco-diesel. employment of manpower will help workers alleviate their standards of living if not at least a stable job to help them in their day to day subsistence. revenues for the government will also increase through the income taxes collected from those newly employed. It will also lessen the country's dependence on crude oil importations by as much as 15%, thus dollar earnings for the government. This will boost the national economy in a way since more dollar or money circulating and being used within the country.